De la eternidad al flujo: apuntes para pensar una filosofía primera desde la temporalidad - Bouroncle, Sebastián (2024)
The following paper attempts to show an overview of the ways in which the concept of “first philosophy” has been appropriated during the history of Western philosophy, first as metaphysics and then as transcendental philosophy. It is maintained that this transformation is accompanied by a paradigm shift in the understanding of time: as an element whose explanation requires its overcoming of eternity as a self-founding original dimension. Likewise, it is argued why this transformation maintains the same guiding thread in the philosophical motives that are found within the concept of “first philosophy” itself.